2020
DOI: 10.3390/cancers12020489
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Tumour Effect of Syk Inhibitor and Olaparib in Squamous Cell Carcinoma: Roles of Syk in EGFR Signalling and PARP1 Activation

Abstract: Syk is a non-receptor tyrosine kinase involved in the signalling of immunoreceptors and growth factor receptors. Previously, we reported that Syk mediates epidermal growth factor receptor (EGFR) signalling and plays a negative role in the terminal differentiation of keratinocytes. To understand whether Syk is a potential therapeutic target of cancer cells, we further elucidated the role of Syk in disease progression of squamous cell carcinoma (SCC), which is highly associated with EGFR overactivation, and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Unlike RIOK2, there is a biological rationale for the non-receptor tyrosine kinase SYK to potentially contribute to erlotinib resistance. SYK positively regulates EGFR and has been shown to be involved in EGFR signaling in squamous cells and ovarian carcinoma, where it contributes to paclitaxel and lapatinib resistance [ 78 , 79 ]. However, it has been reported that SYK possesses both tumor promoter and suppressor roles in human breast carcinoma and that decreased expression is associated with a poor prognosis [ 80 , 81 , 82 ]; thus, SYK inhibition may work either synergistically or antagonistically with erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike RIOK2, there is a biological rationale for the non-receptor tyrosine kinase SYK to potentially contribute to erlotinib resistance. SYK positively regulates EGFR and has been shown to be involved in EGFR signaling in squamous cells and ovarian carcinoma, where it contributes to paclitaxel and lapatinib resistance [ 78 , 79 ]. However, it has been reported that SYK possesses both tumor promoter and suppressor roles in human breast carcinoma and that decreased expression is associated with a poor prognosis [ 80 , 81 , 82 ]; thus, SYK inhibition may work either synergistically or antagonistically with erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that suppression of SYK increases EGFRderived signalling in mammary epithelial cells 63 and phosphorylation of EGFR, JNK, p38 MAPK, STAT1 and STAT3. 64 The findings of epigenetic silencing of SYK's expression and introduction of a senescence phenotype after induced demethylation in subsets of melanoma cell lines suggest that SYK is implicated in establishing and/or maintaining OIS, acting as an oncosuppressor agent. 65 More specifically, p53 as well as p53-dependent p21's activation by SYK repress the phosphorylation of pRB, altogether resulting in tumor growth inhibition.…”
Section: Syk-related Pathwaysmentioning
confidence: 99%
“…From the perspective of oncogenesis, SYK's function has been a matter of investigation lately. It is shown that suppression of SYK increases EGFR‐derived signalling in mammary epithelial cells 63 and phosphorylation of EGFR, JNK, p38 MAPK, STAT1 and STAT3 64 . The findings of epigenetic silencing of SYK's expression and introduction of a senescence phenotype after induced demethylation in subsets of melanoma cell lines suggest that SYK is implicated in establishing and/or maintaining OIS, acting as an oncosuppressor agent 65 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, depletion of NMNAT1, which is involved in the synthesis of NAD+, PARP's substrate, induced DNA damage and sensitized cells to cisplatin but exhibited redundancy with PARPi in this respect [12]. Inhibition of EGFR or Syk (which mediates EGFR signaling) was synergistically cytotoxic in combination with olaparib in squamous cell carcinoma cells suggesting therapeutic potential [13].…”
mentioning
confidence: 99%